1998
DOI: 10.1046/j.1365-2842.1998.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initiator concentration, exposure time and particle size of the filler upon the mechanical properties of a light‐curing radiopaque dental composite

Abstract: Concentration of camphorquinone initiator, exposure time of the light source and particle size of a radiopaque glass filler have been varied for an indigenously developed light-curing dental composite and the changes in the microhardness, compressive strength and diametral tensile strength studied. Higher initiator concentration and exposure times are found to improve the microhardness values while a concentration above 0.25% does not signify any drastic improvement in compressive and diametral strength. Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 7 publications
0
14
0
8
Order By: Relevance
“…It has been reported that the polymerization rate of photo-cure adhesive monomer is dependent on the type and concentration of the photoinitiators. 35,36 Camphorquinone, which is a common photoinitiator in composite resin and adhesive resin, could produce a synergistic effect when combined with another co-initiator and result in an improvement in polymerization conversion. 36 NB contains camphorquinone as a photoinitiator, whereas SE contains camphorquinone and another co-photoinitiator.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the polymerization rate of photo-cure adhesive monomer is dependent on the type and concentration of the photoinitiators. 35,36 Camphorquinone, which is a common photoinitiator in composite resin and adhesive resin, could produce a synergistic effect when combined with another co-initiator and result in an improvement in polymerization conversion. 36 NB contains camphorquinone as a photoinitiator, whereas SE contains camphorquinone and another co-photoinitiator.…”
Section: Discussionmentioning
confidence: 99%
“…Many discussions have taken place about the variables that most influence this stress. According to previous studies, filler volume fraction, 24 polymerization shrinkage, 25 camphorquinone concentration, 26 amine concentration, 27 specimen geometry, 28 and curing method 29 are among many factors considered significant in the development of polymerization shrinkage stresses. With FEA, it is possible to isolate the variables of interest (eg, CF, geometry, volume, area, angle) and to study their individual or combined effects in cases where it is not possible or it is too difficult to perform in an in vitro experiment.…”
mentioning
confidence: 99%
“…The most popular photoinitiator among dental polymers is camphorquinone (CQ) [2,10,[20][21][22][23][24][25][26][27]. CQ has good absorption within the visible region of the light spectrum, with wavelength peak of 470 nm [10].…”
Section: Discussionmentioning
confidence: 99%